History of pre‐pregnancy maternal symptoms of binge eating and childhood behavioral problems in girls and boys. Issue 11 (20th July 2022) - Tapp, Caley; Mishra, Gita D.; Dobson, Annette J.; Moss, Katrina M.; Tooth, Leigh R.
Abstract: Objective: To explore whether children of mothers with pre‐pregnancy binge eating (BE) symptoms have more behavioral difficulties compared with those without and whether associations are moderated by ED symptoms and other maternal health and social factors measured during childhood. Method: Pre‐pregnancy BE symptoms were collected by the Australian Longitudinal Study on Women's Health at Survey 1 (in 1996) and/or at Survey 2 (in 2000) using questions mapped to DSM BE criterion 1. In 2016/7, 2180 women from the 1973–78 cohort provided data on externalizing and internalizing behavior, measured by Strengths and Difficulties Questionnaire, on 4054 of their children (2–12 years) in the Mothers and their Children's Health study. Covariates were markers of other ED symptoms, sociodemographic, social support, and mental health factors collected proximally to the child outcomes. Hierarchical multivariable regression models, using generalized estimating equations accounting for clustering of children within mothers, were used. Results: Pre‐pregnancy BE symptoms were associated with child behavior, with associations only moderated after adjustment for proximal markers of ED (girls internalizing behavior, b (95%CI) .30 (−.02, .61); boys externalizing behavior .34 (−.04, .73)) or social support (girls externalizing behavior 0.26 (−.08, .61)). Pre‐pregnancy BE symptoms were not associated with boys internalizing behavior (−.27 (−.02, 0.57)). Discussion: Studies with repeated ED measures should test hypotheses that these associations vary by timing of ED measurement. Identification of young women at risk of BE symptoms pre‐pregnancy, as well as when children are older, may enable health services, treatment programs, and supports to minimize longer term effects on children. Public significance statement: A history of binge eating symptoms up to 10 years pre‐pregnancy in mothers is associated with behavior problems in their girls and boys at average age of 7. However, the association is moderated by behaviors of eating disorders and social support in the mothers during childhood. Identification of ED symptoms prior to pregnancy, and then after childbirth, might enable health services to intervene to maximize child and mother outcomes.